Evaluasi Pelaksanaan Kebijakan Program Keluarga Harapan (PKH) Dalam Pengentasan Kemiskinan di Kabupaten Tuban - Samian, Samian; Muchsin, Slamet; Afiffuddin, Afiffuddin (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The Family Hope Program (Program Keluarga Harapan or PKH) is established to alleviate poverty among underprivileged communities, particularly in the socio-economic, educational, and healthcare sectors. Research is conducted to examine (1) how the implementation of PKH alleviates poverty; (2) how the implementation of PKH is evaluated; and (3) the supporting and inhibiting factors of PKH in alleviating poverty in Tuban Regency. The research aims to analyze the implementation, evaluate it, and identify the factors involved. The qualitative approach is utilized, employing a case study research design to describe the implementation of PKH events, supported by both primary and secondary sources. Data triangulation techniques are applied to reduce, present, and draw conclusions. The overall results align with the plan, and multi-factor inhibitors can be addressed effectively, leading to the successful implementation of the PKH program. A deep understanding of conventional problems, increased coordination between stakeholders, and good communication are the keys to success in implementing the KPM-PKH assistance program in Bacan District, Tuban Regency